2020
DOI: 10.1007/s00784-019-03157-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperextension of the neck (rose position) on cerebral blood oxygenation in patients who underwent cleft palate reconstructive surgery: prospective cohort study using near-infrared spectroscopy

Abstract: Objectives To facilitate the best approach during cleft palate surgery, children are positioned with hyperextension of the neck. Extensive head extension may induce intraoperative cerebral ischemia if collateral flow is insufficient. To evaluate and monitor the effect of cerebral blood flow on cerebral tissue oxygenation, near-infrared spectroscopy has proved to be a valuable method. The aim of this study was to evaluate and quantify whether hyperextension affects the cerebral tissue oxygenation in children du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In our experience, significant CrSO2 desaturation was observed during a rigid laryngoscopy (due to overextension of the neck) (see Annex, Figure S1A) and during placement of a central venous catheter (due to turning the patient's head, Annex, Figure S2). Indeed, Smarius et al 15 have shown that hyperextension of the neck in children during surgery for cleft palate causes a significant drop of CrSO2. Optimize oxygenation. If the observed decline in CrSO2 coincides with an almost contemporary decrease in SpO2 (usually delayed by 10–15 seconds 16 ) consider an adjustment of FiO2, check of ETT patency 17 or dislocation, consider recruitment maneuvers, and adjustment of ventilator parameters. Optimize EtCO2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experience, significant CrSO2 desaturation was observed during a rigid laryngoscopy (due to overextension of the neck) (see Annex, Figure S1A) and during placement of a central venous catheter (due to turning the patient's head, Annex, Figure S2). Indeed, Smarius et al 15 have shown that hyperextension of the neck in children during surgery for cleft palate causes a significant drop of CrSO2. Optimize oxygenation. If the observed decline in CrSO2 coincides with an almost contemporary decrease in SpO2 (usually delayed by 10–15 seconds 16 ) consider an adjustment of FiO2, check of ETT patency 17 or dislocation, consider recruitment maneuvers, and adjustment of ventilator parameters. Optimize EtCO2.…”
Section: Resultsmentioning
confidence: 99%
“…In our experience, significant CrSO2 desaturation was observed during a rigid laryngoscopy (due to overextension of the neck) (see Annex, Figure S1A) and during placement of a central venous catheter (due to turning the patient's head, Annex, Figure S2). Indeed, Smarius et al 15 have shown that hyperextension of the neck in children during surgery for cleft palate causes a significant drop of CrSO2.…”
Section: Scrupulous Attention Is Paid To Avoid Compression By Body Su...mentioning
confidence: 99%
“…The monitoring was applied before induction of anesthesia to obtain a baseline value as it is recommended to act upon changes from baseline (<20%) and trends in NIRS readings rather than an absolute number [ 1 ]. NIRS has been found to detect intraoperative cerebral desaturation in surgeries requiring extensive head rotation or extension [ 5 ]. In situations where the collateral carotid flow may be depleted due to external compression or surgical manipulation similar to our setting, NIRS may serve as a guide for the safe positioning of the patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant drop in cerebral oxygenation after positioning. However it is not clear whether this drop is truly significant physiologically in the American Society of Anaesthesiologists' (ASA) class 1 and 2 patients and none of the children had a neurological disturbance (12).…”
Section: Discussionmentioning
confidence: 99%